Distribution of HLA class 1 antigens in normal human tissue and in mammary cancer. Issue 7 (July 1981) - Fleming, K A; McMichael, A; Morton, J A; Woods, J; McGee, J O
Abstract : With a monoclonal antibody which reacts with all HLA class 1 antigens it was found that these antigens are not uniformly distributed in all nucleated cells. Rather HLA class 1 antigens are restricted in their distribution to lymphoid cells, endothelial cells of small vessels, and certain epithelia including mammary duct cells. These antigens were not detected on hepatocytes, specialised cells of the central nervous system, or on the tumour cells of 8 out of 17 human mammary cancers. Given the hypothesis that T cells only respond to foreign antigens on cells which share a common major histocompatibility antigen, these results imply that the T cell responses to viral infections of hepatocytes–for example, hepatitis B virus and the CNS–for example, subacute sclerosing encephalitis, are mediated through an antigen system other than HLA class 1. The absence of HLA class 1 antigen on many mammary cancer cells may be of prognostic significance if T cell modulation of tumour growth is mediated through this class of antigens.